Humanistic formation for nursing care - Furegato, Antonia Regina Ferreira; Scatena, Maria Cecilia Morais (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2005)
Attending to the current need for nursing care humanization, our teaching on the interpersonal nurse/patient relation is based on a humanistic theoretical reference framework. Each meeting works as a laboratory, expanding cognitive, intuitive and affective knowledge on the contents, technique and feelings in each experience. A five-item questionnaire was used to evaluate how learning reflected in professional actions. The results reveal the impact of learning on teaching, research and care, on new teaching and research strategies.